2016
DOI: 10.1111/1753-6405.12407
|View full text |Cite
|
Sign up to set email alerts
|

The impact of migration on deaths and hospital admissions from work‐related injuries in Australia

Abstract: Objective: The shift from an industrial to a service‐based economy has seen a decline in work‐related injuries (WRIs) and mortality. How this relates to migrant workers, who traditionally held high‐risk jobs is unknown. This study examined deaths and hospital admissions from WRI, among foreign and Australian‐born workers. Methods: Tabulated population data from the 1991 to 2011 censuses, national deaths 1991–2002 and hospital admission for 2001–10. Direct age standardised mortality and hospital admission rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…This finding is similar to work from Spain that found that migrant workers had a higher prevalence of precariousness at work than native-born workers (77.1 vs. 45.2%, p < 0.001), particularly among young, female immigrant workers (88.6%) [ 24 ]. Similarly, a lower prevalence of US-born agricultural workers reported insecure work compared with foreign-born workers [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to work from Spain that found that migrant workers had a higher prevalence of precariousness at work than native-born workers (77.1 vs. 45.2%, p < 0.001), particularly among young, female immigrant workers (88.6%) [ 24 ]. Similarly, a lower prevalence of US-born agricultural workers reported insecure work compared with foreign-born workers [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other possibly important contributing factors could be (1) the shift from a manufacturing and industrial economy to a service-based one. According to our data analysis, the number of workers in the manufacturing industry in South Australia reduced about 18% during 2000-2014, meanwhile there has been about a 10% increase in the community services sector during the same period; (2) the shift from manual work to automation [21], which has led to a reduction of workers exposed to hazardous workplace conditions. In the process of deindustrialisation, a gradual decline in work-related morbidity and mortality has also been observed in other developed countries such as USA [22] and Canada [23]; and (3) the tightening eligibility for compensation benefits overtime.…”
Section: A Downward Trend: Implications For Intervention Effectivenesmentioning
confidence: 96%
“…In contrast, in Australia, native-born workers are more likely to work in agriculture and construction, likely due to the push for "skilled" or professional migration to Australia, referring to workers with skills that will contribute to the Australian economy. Consequently, occupational injury may be higher among native-born than foreign-born workers in Australia (85).…”
Section: Occupational Health Risks For Immigrant Workersmentioning
confidence: 99%